Intelligent robotics systems: inspiring the NEXT 16th FIRA RoboWorld Congress, FIRA 2013, Kuala Lumpur, Malaysia, August 24-29, 2013 : proceedings - Khairuddin Omar (Communications in computer and information science, 2013)
This book constitutes the refereed proceedings of the 16th FIRA Robo World Congress, FIRA 2013, held in Kuala Lumpur, Malaysia, in August 2013. The congress consisted of the following three conferences: 5th International Conference on Advanced Humanoid Robotics Research (ICAHRR), 5th International Conference on Education and Entertainment Robotics (ICEER), and 4th International Robotics Education Forum (IREF). The 38 revised full papers presented were carefully reviewed and selected from 112 submissions. They cover various topics related to the technical developments and achievements in the field of robotics.